Polyphenolic Glycosides and Aglycones Utilize Opposing Pathways To Selectively Remodel and Inactivate Toxic Oligomers of Amyloid β - Ladiwala, Ali Reza A. (2011)
Substantial evidence suggests that soluble prefibrillar oligomers of the Aβ42 peptide associated with Alzheimer’s disease are the most cytotoxic aggregated Aβ isoform. Limited previous work has revealed that aromatic compounds capable of remodeling Aβ oligomers into non-toxic conformers typically do so by converting them into off-pathway aggregates instead of dissociating them into monomers. Towards identifying small molecule antagonists capable of selectively dissociating toxic Aβ oligomers into soluble peptide at substoichiometric concentrations, we have investigated the pathways used by polyphenol aglycones and their glycosides to remodel Aβ soluble oligomers. We find that eleven polyphenol aglycones of variable size and structure utilize the same remodeling pathway whereby Aβ oligomers are rapidly converted into large, off-pathway aggregates. Strikingly, we find that glycosides of these polyphenols all utilize a distinct remodeling pathway in which Aβ oligomers are rapidly dissociated into soluble, disaggregated peptide. This disaggregation activity is a synergistic combination of the aglycone and glycone moieties since combinations of polyphenols and sugars fail to disaggregate Aβ oligomers. We also find that polyphenolic glycosides and aglycones use the same opposing pathways to remodel Aβ fibrils. Importantly, both classes of polyphenols fail to remodel non-toxic Aβ oligomers (which are indistinguishable in size and morphology to Aβ soluble oligomers) or promote aggregation of freshly disaggregated Aβ peptide, revealing that they are specific for remodeling toxic Aβ conformers. We expect that these and related small molecules will be powerful chemical probes for investigating the conformational and cellular underpinnings of Aβ-mediated toxicity.